Longitudinal Spending on Endovascular and Open Abdominal Aortic Aneurysm Repair. Issue 5 (May 2020) - Trooboff, Spencer W.; Wanken, Zachary J.; Gladders, Barbara; Columbo, Jesse A.; Lurie, Jon D.; Goodney, Philip P.
Abstract : Background: Endovascular repair (EVR) has replaced open surgery as the procedure of choice for patients requiring elective abdominal aortic aneurysm (AAA) repair. Long-term outcomes of the 2 approaches are similar, making the relative cost of caring for these patients over time an important consideration. Methods and Results: We linked Medicare claims to Vascular Quality Initiative registry data for patients undergoing elective EVR or open AAA repair from 2004 to 2015. The primary outcome was Medicare's cumulative disease-related spending, adjusted to 2015 dollars. Disease-related spending included the index operation and associated hospitalization, surveillance imaging, reinterventions (AAA-related and abdominal wall procedures), and all-cause admissions within 90 days. We compared the incidence of disease-related events and cumulative spending at 90 days and annually through 7 years of follow-up. The analytic cohort comprised 6804 EVR patients (median follow-up: 1.85 years; interquartile range: 0.82–3.22 years) and 1889 open repair patients (median follow-up: 2.62 years; interquartile range: 1.13–4.80 years). Spending on index surgery was significantly lower for EVR (median [interquartile range]: 25 924 [22 280–32 556] EVR versus 31 442 [24 669–40 419] open; P <0.001), driven by a lower rate of in-hospital complications (6.6% EVR versus 38.0% open; P <0.001). EVR patients underwent more surveillance imaging (1.8 studies per person-year EVR versus 0.7 studies per person-year open; P <0.001) and AAA-related reinterventions (4.0 per 100 person-years EVR versus 2.1 per 100 person-years open; P =0.041). Open repair patients had higher rates of 90-day readmission (12.9% EVR versus 17.8% open; P <0.001) and abdominal wall procedures (0.6 per 100 person-years EVR versus 1.5 per 100 person-years open; P <0.001). Overall, EVR patients incurred more disease-related spending in follow-up (7355 EVR versus 2706 open through 5 years). There was no cumulative difference in disease-related spending between surgical groups by 5 years of follow-up (−33 EVR [95% CI: −1543 to 1476]). Conclusions: We observed no cumulative difference in disease-related spending on EVR and open repair patients 5 years after surgery. Generalized recommendations about which approach to offer elective AAA patients should not be based on relative cost. Abstract : Supplemental Digital Content is available in the text.